The impact of anxiety upon cognition: perspectives from human threat of shock studies - Robinson, Oliver J.; Vytal, Katherine; Cornwell, Brian R.; Grillon, Christian (Frontiers in Human Neuroscience, 2013)
Anxiety disorders constitute a sizeable worldwide health burden with profound social and economic consequences. The symptoms are wide-ranging; from hyperarousal to difficulties with concentrating. This latter effect falls under the broad category of altered cognitive performance; in this review we examine studies quantifying such impacts of anxiety on cognition. Specifically, we focus on the translational threat of unpredictable shock paradigm, a method previously used to characterize emotional responses and defensive mechanisms that is now emerging as valuable tool for examining the interaction between anxiety and cognition. In particular, we compare the impact of threat of shock on cognition in humans to that of pathological anxiety disorders. We highlight that both threat of shock and anxiety disorders promote mechanisms associated with harm avoidance across multiple levels of cognition (from perception to attention to learning and executive function) – a ‘hot’ cognitive function which can be both adaptive and maladaptive depending upon the circumstances. This mechanism comes at a cost to other functions such as working memory, but leaves some functions, such as planning, unperturbed. We also highlight a number of cognitive effects that differ across anxiety disorders and threat of shock. These discrepant effects are largely seen in ‘cold’ cognitive functions involving control mechanisms and may reveal boundaries between adaptive (e.g. response to threat) and maladaptive (e.g. pathological) anxiety. We conclude by raising a number of unresolved questions regarding the role of anxiety in cognition that may provide fruitful avenues for future research.